Behaviour of PM10 and some metals in atmospheric aerosols in the southeastern Spain (Malaga) - Fernández, Mª Carmen; Pérez-Martínez, Manuel; Dueñas-Buey, Mª Concepción; Liger-Pérez, Esperanza; Gordo Puertas, Elisa; Cañete-Hidalgo, Sergio Andrés (My University, 2014)
INTRODUCTION. Studies in aerosol particles provide a means for evaluating the integrated effects of transport and meteorology on the atmospheric loadings of substances with different sources in little industrialised area in South Spain. Weekly samples of aerosols in air were continuously monitored between 2009 and 2011 in Malaga (Spain) with a high-volume air sampler (ASS-500C). Additionally, levels of particulate matter fraction PM10 were monitored in one of the Atmospheric Pollution Monitoring network managed by the Environmental Health Service of the Andalusian Government. The sampling point (4º 28’ 4” W; 36º 43’ 40”N) was located approximately 5 km from the coastline, near the airport and surrounded by roads with traffic exhaust. The high-volume sampler uses polypropylene square filters (44 x 44 cm2) with a collection efficiency of 93-99%, at a flow rate of 90,000 L min-1 This system was configured to filter a discharge average of 600 m3/h of air. The average weekly volume ranged from 65000 to 90000 m3. The dust content in the filters was calculated gravimetrically by weighing the filters before and after and were analysed for the major elements Ca, Fe, Na, Mg, K, Cu, Ni, Cr, Zn and Pb by ICP-MS (NexION).
Keywords: Deposición atmosférica; PM10; Metals; Natural origins; Anthropogenic origins